Parallel empathy and group attitudes in late childhood: The role of perceived peer group attitudes. Issue 3 (4th May 2021) - van Bommel, Ghislaine; Thijs, Jochem; Miklikowska, Marta
ABSTRACT: Although several studies have examined outgroup empathy, the link between trait empathy and outgroup attitudes has been underinvestigated. In the present study this link was investigated among two samples of ethnic Dutch preadolescents ( N = 335, Mage = 10.83 years, SD = 0.94; 53% girls; N = 326; Mage = 10.53 years, SD = 1.03; 48% girls). It examined children's parallel empathy in relation to their ethnic attitudes, and the moderating role of perceived peer norms. Results (partly) support the hypotheses that empathy is associated with more outgroup positivity and less ingroup bias (ingroup minus outgroup attitude). The negative link between empathy and outgroup bias was stronger when peers were perceived to be more biased against the outgroup.